(untitled) (Bangladesh Journal of Animal Science, 2013)
To investigate the prevalence of gastrointestinal parasites of calves, 450 feacal samples were collected from Mirsarai Upazilla of Chittagong District of Bangladesh during the period from 2011 to 2012. Fecal samples of calves aged up to 6 months of three different genotypes were examined for gastrointestinal parasites. The results of faecal examination revealed that 54.22% calves were infected with some of the parasites. Toxocara spp (22.66%), Eimeria spp (17.33%), Strongyloides spp (6.44%), gastrointestinal strongyles (3.78%), Moniezia spp (01.78%), Trichuris spp (01.56%) and Fasciola gigantica (0.66%) were found. We found eggs of Toxocara spp eggs, Strongyloides spp eggs and oocysts of Eimeria spp during the age of first month, gastrointestinal strongyles eggs and Moniezia eggs at/during/within the age of 3 months and eggs of Trichuris spp and Fasciola gigantic during the age of five months of age. Prevalence of gastrointestinal parasites in Local, Shahiwal cross and Holstein Frisian cross were 46%, 52% and 62%, respectively. The age and genotype of the calves and the locality of investigations might have influenced the prevalence of the parasitic infections. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18494 Bang. J. Anim. Sci. 2013. 42 (2): 139-142